(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article provides information about the military management system of Amir Temur in Mu’iniddin Natanzi’s «Muntahab ut-Tavarikhi Mu’ini» and scientific research works, treatises, and scientific-literary publications conducted by Russian Temur scientists. At the same time, in the following years, special attention was paid to the issues of truthful coverage of Amir Temur’s personality.